A comparative study of radar and optical observations of meteor showers using SAAMER-OS and CAMS. (1st September 2020) - Bruzzone, Juan Sebastián; Janches, Diego; Jenniskens, Peter; Weryk, Robert; Hormaechea, Jose Luis
Abstract: We present a comparison of radar and optical meteor shower radiant distributions with the Southern Argentina Agile Meteor Radar-Orbital System (SAAMER-OS) and the Cameras for Allsky Meteor Surveillance (CAMS). This study comprise seven years of meteor radar surveillance with SAAMER-OS and over eight years of the CAMS video meteor data. In total, over five million meteor radar and close to 500, 000 video meteor orbits are analyzed thus providing a robust statistical dataset. With a five-fold increase in SAAMER-OS orbits, we revisit the initial SAAMER-OS shower survey and compare a selection of 20 established meteor showers against those reported by CAMS.